RELEVANSI PEMBUATAN KEPUTUSAN DALAM ORGANISASI PENDIDIKAN ISLAM - Didin Sirojudin (Universitas KH. A. Wahab Hasbullah Tambakberas Jombang, 2019)
Organization and leadership related to decision making. So leaders have authority in decision making. In reality if in the leadership of Islamic educational institutions, there is still a madrasa head running his leadership with all-mono policies, namely monomanagement, monokepemership, monocepecial, and so forth, then this situation will cause the impression of being less organized and authoritarian. The organization will only function if the leaders have the ability to make decisions, and instruct its implementation to members of the organization in accordance with their area of ​​duties and responsibilities. Decisions in Islamic educational institutions are steps to solve the problems that exist when designing an education to achieve goals.